2018
DOI: 10.1002/pros.23747
|View full text |Cite
|
Sign up to set email alerts
|

HOXB13 interaction with MEIS1 modifies proliferation and gene expression in prostate cancer

Abstract: Background The recurrent p.Gly84Glu germline mutation (G84E) in HOXB13 is consistently associated with prostate cancer (PCa), although the mechanisms underlying such linkage remain elusive. The majority of the PCa‐associated HOXB13 mutations identified are localized to two conserved domains in HOXB13 that have been shown to mediate the interaction with MEIS cofactors belonging to the TALE family of homeodomain transcription factors. In this study, we sought to interrogate the biochemical and functional interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 47 publications
1
35
0
1
Order By: Relevance
“…Further, the HOXB13 G84E mutation is associated with an increased odds ratio (OR) for colorectal cancer (OR: 2.8, p=0.02), bladder cancer (OR: 1.99, p=0.06), and leukemia (OR: 3.17, p=0.01), further demonstrating the importance of the need to understand how HOXB13 mutations promote cancer ( Akbari et al, 2013 ; Beebe-Dimmer et al, 2015 ). A recent study did not detect an effect of the G84E mutation on interaction with MEIS1 ( Johng et al, 2019 ), suggesting alternative mechanisms for HOXB13 mutations in driving prostate carcinogenesis beyond disruption of MEIS interaction. Thus, further research is needed to define the transcriptional impact of HOXB13 mutations on MEIS interaction and the regulation of MEIS–HOXB13-associated gene targets.…”
Section: Discussionmentioning
confidence: 93%
“…Further, the HOXB13 G84E mutation is associated with an increased odds ratio (OR) for colorectal cancer (OR: 2.8, p=0.02), bladder cancer (OR: 1.99, p=0.06), and leukemia (OR: 3.17, p=0.01), further demonstrating the importance of the need to understand how HOXB13 mutations promote cancer ( Akbari et al, 2013 ; Beebe-Dimmer et al, 2015 ). A recent study did not detect an effect of the G84E mutation on interaction with MEIS1 ( Johng et al, 2019 ), suggesting alternative mechanisms for HOXB13 mutations in driving prostate carcinogenesis beyond disruption of MEIS interaction. Thus, further research is needed to define the transcriptional impact of HOXB13 mutations on MEIS interaction and the regulation of MEIS–HOXB13-associated gene targets.…”
Section: Discussionmentioning
confidence: 93%
“…We sought to examine the genetic contribution of MYC to the development and progression of primary PCa in the context of dysregulated growth by using anti-MYC immunohistochemistry and performing laser capture microdissection on populations of human prostate tumor cells with varying 6 expression of MYC protein. We show using transcriptome profiling that increased MYC activity is inversely correlated with expression of Myeloid Ecotropic viral Insertion Site 1 (MEIS1), a transcription factor that interacts with and regulates the activity of HOX homeodomain transcription factors, including HOXB13 [18][19][20]. We determined that MYC binding to the MEIS1 locus decreases as MYC levels increases, and that MEIS1 expression is negatively correlated with HOXB13 expression and AR activity.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, Bhanvadia et al [19] reported that tumors with increased MEIS1 are potentially less aggressive, based on studies of LAPC-4 prostate cancer cells expressing shRNA against MEIS1 and that tumors with lower levels of MEIS1 were at greater risk of biochemical recurrence. HOXB13, a homeodomain transcription factor, has been shown to regulate AR activity while shRNA against HOXB13 in LAPC4 cells inhibits their growth [18]. Based on these prior findings, as HOXB13 physically interacts with MEIS1 [18], tumors expressing less MEIS1 would be expected to display 21 greater HOXB13 expression and AR activity.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We sought to examine the genetic contribution of MYC to the development and progression of primary PCa in the context of dysregulated growth by using anti-MYC immunohistochemistry (IHC) and performing laser capture microdissection on populations of human prostate tumor cells with varying expression of MYC protein. We show using transcriptome profiling that increased MYC activity is inversely correlated with expression of Myeloid Ecotropic viral Insertion Site 1 ( MEIS1 ), a transcription factor that interacts with and regulates the activity of HOX homeodomain transcription factors, including HOXB13 [ 18 20 ]. We determined that MYC binding to the MEIS1 locus decreases as MYC levels increase, and that MEIS1 expression is negatively correlated with HOXB13 expression and AR activity.…”
Section: Introductionmentioning
confidence: 99%